Timeshare Industry Leadership and Human Resource Implications of Employee and Guest Satisfaction - Maier, T.; Gursoy, D (2013)
The Timeshare/Vacation Ownership industry represents a significant component of the Hospitality sector. While similarities exist between traditional Lodging resort operations and leadership practice certain differences exist within the Timeshare industry. This case study sets forth to examine those similarities and differences while emphasizing the critical nature of human resource leadership practice and strategic decision-making scenarios. Specifically, the case focuses on the area of facilities maintenance, employee and customer satisfaction. Research reports are presented which examine employee and guest satisfaction levels across the various company operating units. Results are presented for students to consider, discuss and formulate potential strategic decisions that impact the future outlook of the organization.